Analisa User Experience Sistem KKN Menggunakan Metode Heart Metrics dan Importance Performance Analysis (IPA) - Ananda, Dhea; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah; Fronita, Mona (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
In 2023, the Community Service Program (KKN) system at Sultan Syarif Kasim Riau State Islamic University (UIN Suska Riau) found several significant obstacles based on user feedback. These include prolonged server downtime, difficulty accessing KKN locations, as well as errors and login issues that affect the efficiency of using the system during registration. To address these issues, research was conducted using two methods: HEART Metrics and Importance-Performance Analysis (IPA). HEART Metrics measures user experience through the variables of Happiness, Engagement, Adoption, Retention, and Task Success. IPA identifies improvement priorities by mapping item performance against their importance to users. The results showed that the level of usability based on the HEART variables (Happiness, Engagement, Retention, and Task Success) was classified as "Medium", while Adoption was in the "High" category. Further analysis showed that 9 out of 20 items require improvement, including user satisfaction, attractive design, convenience, accessibility, feature optimization, system quality, site selection, error reduction, and efficiency. These results indicate that the user experience of UIN Suska Riau's KKN system needs to be improved by addressing the items mentioned.